MAKNA EKOLOGIS RITUS BARONG WAÉ TÉKU PADA MASYARAKAT KAMPUNG NGALO MANGGARAI, NTT - Nanur, Bertiana; Lega, Fransiskus Sales (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2023)
The environment is a home for all of God's creation. The environmental crisis today is a cirisis of the home all of God's creation. The crisis was caused primarily by human attitudes and actions that were not wise and environmentally friendly. This research seeks to explore the local wisdom of the Manggarai people in relation to the environment. Manggarai people have a very deep affinity with nature. The local wisdom studied in this research is the barong waé téku tradition in Manggarai. The method used in collecting and analyzing data is qualitative research. The research data was obtained through in-depth interviews with the informants. Based on the data collected and analyzed, the researcher found that the practice of barong waé téku culture in Manggarai has important implications for efforts to save the environment from the crisis. Based on the findings of this study, the barong waé téku tradition teaches the people of Manggarai about water as a source of life. Water is a symbol of God. Through the barong waé téku ritual, the people of Manggarai express their gratitude to God and ask for an abundance of water for their next life. In addition, the barong waé téku ritual awakens the Manggarai people to always preserve the environment, especially around springs. The barong waé téku rite is interpreted as an effort to save the environment from the crisis.